The Effect of the Experiential Learning Model on Elementary School Students’ IPAS Learning Outcomes: Pengaruh Model Pembelajaran Experiential Learning Terhadap Hasil Belajar IPAS Siswa Sekolah Dasar - Anggriani, Meri; Sulaiman, Sulaiman; Hasan, Hasan (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2026)
This study investigates the effect of the Experiential Learning model on the integrated science and social studies (IPAS) learning outcomes of elementary school students within the framework of the Indonesian Merdeka Curriculum. A pre-experimental one-group pretest–posttest design was employed involving 18 fourth-grade students from SD Negeri 01 Woja, who completed a validated 20-item multiple-choice test on IPAS concepts. Descriptive statistics showed an increase in mean scores from 56.94 (pretest) to 79.44 (posttest). A Shapiro–Wilk test on the difference scores indicated that the normality assumption was met, and a paired samples t-test revealed a statistically significant improvement in achievement, t(17) = −13.029, p < 0.001, with a large effect size (Cohen’s d = 2.25). These findings suggest that experiential learning is associated with substantial gains in IPAS achievement; however, given the pre-experimental design without a control group, causal claims must remain tentative. The study highlights the potential of experiential learning for supporting the implementation of the Merdeka Curriculum in non-urban schools, while underlining the need for structured instructional modules, teacher training, and further studies with stronger designs, larger and more diverse samples, and additional non-cognitive outcome measures.